EFEKTIVITAS METODE PEMBELAJARAN GAMES-BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SD SWASTA HKBP TOMUAN - Simanjuntak, Melvin; Joe Reinata Tarigan; Sri Tetty Simanjuntak; Yohana Inriani Malau; Noni Epitasari Damanik; Elsa Tri Yunita Simbolon; Juwita Nainggolan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to assess the effectiveness of the Game Based Learning method. In this increasingly advanced era, the use of technology in education is increasing, this also has an impact on learning methods which are increasingly varied, the games best learning method is a method that is often used. This method is expected to create fun, interesting and interactive learning so that it can increase students' learning motivation. This research uses a qualitative approach with an experimental design to measure the increase in student learning motivation before and after implementing the learning-based method.